RUNX1 expression dynamics in plasma cell differentiation and pathogenesis of multiple myeloma - Tang, Ting Fang; Chan, Yee Teng; Lim, Hui Jing; Cheok, Yi Ying; Anuar, Nur Adila; Cheong, Chin Sum; Looi, Chung Yeng; Tan, Sen Mui; Wong, Won Fen; Gan, Gin Gin (Frontiers in Immunology, 2025)
Multiple myeloma (MM) is characterized by the malignant proliferation of plasma cells within the bone marrow. The transcriptional mechanisms governing plasma cell differentiation and MM pathogenesis are regulated by an intricate network of transcription factors, the role of RUNX1 in this process remains poorly defined. This study aimed to characterize plasma cell subsets in MM and evaluate the expression and functional role of RUNX1 during B cell differentiation. Bone marrow and peripheral blood samples were collected from 61 MM patients and 18 healthy donors. Flow cytometry was used to identify B cell and plasma cell subsets and measure RUNX1 expression across B cell maturation stages. Functional validation was conducted via siRNA-mediated RUNX1 knockdown in CD19+ B cells followed by in vitro plasma cell differentiation assays. Our data showed that MM patients exhibited significantly increased proportions of plasma cells in bone marrow compared to healthy controls. Intriguingly, RUNX1 expression was low in naive B cell subsets but increased progressively through plasmablast, pre-plasma, and plasma stages. Although RUNX1 expression did not significantly differ across MM stages or between newly diagnosed and relapsed/refractory cases, plasmablasts from MM patients showed higher RUNX1 levels than those from controls. Knockdown of RUNX1 in vitro using siRNA delayed B cell differentiation transiently. In summary, RUNX1 expression is dynamically upregulated during terminal B cell differentiation and is elevated in MM-derived plasmablasts. These findings provide new insights into a potential role for RUNX1 in the B cell differentiation axis and MM disease progression.